Building Framework of Work Engagement Social Welfare Institution in Gayo Lues Atjeh - Tati Nugrahati; Mochamad Soelton; Yanto Ramli; Tantri Yanuar Rahmat Syah; Eko Tama Putra Saratian; Harefan Arief; Febry Nur Fauzi (Forum Inovasi Bisnis dan Manajemen, 2019)
This study aims to examine and analyze the influence of Organizational Culture, Job Insecurity, Organizational Commitment, Psychological Meaningfulness Towards Work Engagement in Social Welfare Institutions (LKS) of Central Aceh District, Takengon and Gayo Lues. The research in done through the distribution of questionnaires, and the population of this research is consisted of the employees in the Central Aceh Regency Social Welfare Institution (LKS), Takengon and Gayo Lues. That was done to 50 respondents using a quantitative descriptive approach. The approach used in this research is Structural Equation Model (SEM) with Smart-PLS analysis tools 3.0. The results of this study are that organizational culture, Psychological meaningfulness, Organizational commitment has a significant positive effect on work engagement, and only Job Insecurity has a significant negative effect on work engagement.